Hadith, “the Imamate is from Quraish” in the face of contemporary challenges - Al-Khayrabadi, Mohammed Abul Lais; Ibrahim, Esam Eltigani Mohamed (2014)

(untitled)
The meanings of certain prophetic hadiths are ambiguous as a result of an apparent conflict with the spirit of the age. Among such hadiths is the hadith advocating that the imamate is from Quraish. There are several prophetic iadiths advocating that the highest level of political leadership belongs to Quraish. Furthermore, there is a consensus among the companions and ta’biʿiīn to this effect, in addition to a general agreement among the majority of scholars. It would seem that only the Kharijites and some Mu’tazilites and Ash’arites would disagree with this. However, this concept faces a number of challenges in today’s age in light of the spirit of equality and equal opportunity.